2008
DOI: 10.2337/db08-0700
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants in the Adiponectin Gene (ADIPOQ) Associated With Plasma Adiponectin Levels, Type 2 Diabetes, and Diabetes-Related Quantitative Traits

Abstract: OBJECTIVE-Variants in ADIPOQ have been inconsistently associated with adiponectin levels or diabetes. Using comprehensive linkage disequilibrium mapping, we genotyped single nucleotide polymorphisms (SNPs) in ADIPOQ to evaluate the association of common variants with adiponectin levels and risk of diabetes. RESEARCH DESIGN AND METHODS-Participants in theFramingham Offspring Study (n ϭ 2,543, 53% women) were measured for glycemic phenotypes and incident diabetes over 28 years of follow-up; adiponectin levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
162
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(182 citation statements)
references
References 25 publications
13
162
7
Order By: Relevance
“…The Framingham Offspring Study, which systematically examined the associations with 22 SNPs that captured all common variation at r 2 . 0.8 across ADIPOQ and its flanking regions, observed that adiponectin level was significantly associated with SNPs in two different regulatory regions, the 5 ′ -promoter (rs17300539) and the 3 ′ -untranslated regions (rs6773957) (17). A recent study dissecting the genetic architecture of plasma adiponectin suggested that two ADIPOQ variants (rs17300539 and rs182052) exhibited independent association (18), and a recent GWAS of 4659 European individuals suggested association with at least nine SNP groups near ADIPOQ (29) Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Framingham Offspring Study, which systematically examined the associations with 22 SNPs that captured all common variation at r 2 . 0.8 across ADIPOQ and its flanking regions, observed that adiponectin level was significantly associated with SNPs in two different regulatory regions, the 5 ′ -promoter (rs17300539) and the 3 ′ -untranslated regions (rs6773957) (17). A recent study dissecting the genetic architecture of plasma adiponectin suggested that two ADIPOQ variants (rs17300539 and rs182052) exhibited independent association (18), and a recent GWAS of 4659 European individuals suggested association with at least nine SNP groups near ADIPOQ (29) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several SNPs including rs17300539 (211391G.A), rs2241766 (+45T.G) and rs1501299 (+276G.T) have been reproducibly reported to be associated with circulating adiponectin (11)(12)(13)(14)(15)(16). Two reports suggested the presence of distinct association signals for adiponectin levels represented by 5 ′ -promoter SNP rs17300539 and either rs6773957 (17) or rs182052 (18), and a gene-wide tagSNP investigation revealed that two haplotype blocks mapping to the ADIPOQ promoter and the relevant exons showed association with adiponectin (19). Only limited evidence has been provided for the functional relevance of these SNPs (20,21), and the common genetic variants identified thus far explain only a fraction of the estimated heritability for adiponectin (22).…”
Section: Introductionmentioning
confidence: 99%
“…In the Framingham Offspring study, 35 two SNPs in the promoter region of ADIPOQ (rs822387, rs17300539) were shown to be strongly associated with plasma adiponectin level, whereas rs17366743 (Tyr111His) was associated with the prevalence of type II diabetes. However, in this study, none of these three SNPs was associated with adiponectin level or hyperglycemia in the screening population.…”
Section: Adipoq Snps and Adiponectin Levelmentioning
confidence: 99%
“…We also addressed the issue of whether or not circulating adiponectin isoforms share a common genetic background with ACR and, if so, if it is partly explained by ADIPOQ gene variability. To this latter purpose, we genotyped single nucleotide polymorphisms (SNPs) in the ADIPOQ gene or their proxies (as indicated by r 2 >0.9) (see Electronic supplementary material [ESM] Table 1), which have been consistently associated with adiponectin levels [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%